REAGENT SAFETY STOCK ANALYSIS (A Case Study of Pharmaceutical Company in Bandung, Indonesia) - Gianfranco, Joshua; Kurnia, Reni; Oktaviani, Rizka; Shafira, Windu Alfianti; Lukitasari, Kiki; Hartati, Verani (CENTRAL ASIA AND THE CAUCASUS, 2022)
Inventory management is a system in which inventory management is carried out, things that include how inventory items are classified and how accurate inventory record keeping data can be maintained. Reagents in pharmaceutical companies, especially in the laboratory, can be said to be the main process of standardization of medicine. To optimize the standardization process in the laboratory, there needs to be a guarantee of the availability of reagents that can meet every standardization process requirement in the laboratory. PT XYZ is one of the leading pharmaceutical companies in Indonesia. Currently, this company is still trying to optimize the management of reagent raw materials, so that the problem of unavailability of materials can be avoided. This study aims to classify each reagent used by the laboratory of PT. XYZ uses the ABC classification. This classification aims to find out the types of reagents that are the top priority of inventory managers. The next step is to carry out optimization of inventory policy on reagent materials that enter class A, namely by determining the value of safety stock and reorder points for each type of reagent. From the classification stage, it is produced that class A consists of 6 types of reagents, namely 11.3% of the 53 types of reagents managed by the company. Class B and Class C are 20 and 27 types of reagents, respectively. Obtained the amount of safety stock for each type of reagent in class A, which is 9 bottles for Acetonitrile,11 bottles for Methanol HPLC, 1 bottle for Alcohol Anhydrous. As for combititrant, HCL 37% and methanol dried, no safety stock is needed because demand is deterministic. With the safety stock value, the company can set a reorder point (ROP) for each type of reagent.